Respuesta :

∑ Hey, montaviapierc)

Answer:

-21

Step-by-step explanation:

Given:

Evaluate each expression if a = 2, b = -3, and c=4.

b ²- ( c² -a²)

Solve:

Since, it given that;

b²-(c²-a²) and a = 2, b = -3 , c = 4.

Therefore, we can substitute to find the answer.

-3² - ( 4² - 2²)

Following the PEMDAS:

  • Parentheses
  • Exponents
  • Multiplication
  • Division
  • Addition
  • Subtraction

-3² - ( 4² - 2²)

= -3² -12

= -9 - 12

= -21

Hence, the answer is - 21.

xcookiex12

8/17/2022

ACCESS MORE